2014
DOI: 10.1177/0020764014548287
|View full text |Cite
|
Sign up to set email alerts
|

The impact of insight on social functioning in patients with schizophrenia

Abstract: Insight has a significant impact on social functioning in schizophrenia, and some, but not all, insight dimensions have direct impact on social performance, independent of their association with symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
3
26
1
1
Order By: Relevance
“…Consistent with this, better clinical insight was correlated with better personal and social skills 65 and prosocial behavior 66 . Montemagni et al 67 found that clinical insight predicted the capacity for social connectedness and may mediate the relationship of negative symptoms to social function.…”
Section: Insight and Outcomesupporting
confidence: 61%
“…Consistent with this, better clinical insight was correlated with better personal and social skills 65 and prosocial behavior 66 . Montemagni et al 67 found that clinical insight predicted the capacity for social connectedness and may mediate the relationship of negative symptoms to social function.…”
Section: Insight and Outcomesupporting
confidence: 61%
“…In a study of patients with schizophrenia, McGurka and Meltzer found that unemployed patients’ negative symptoms and functioning were worse in comparison to the other groups who were employed. Erol et al . found that the employed schizophrenic patients in their study had higher functionalities compared to the unemployed patients.…”
Section: Discussionmentioning
confidence: 75%
“…Marriage increased functional remission. Erol et al . found that the marital status of patients with schizophrenia was found to be higher than that of single patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 Şizofreni hastalarında iç görü olmaması, toplumsal işlevselliği, hastalığın gidişini, tedavi uyumunu olumsuz yönde etkilemektedir. 21 Anosognozi, kişinin hasta olduğunu fark etme yeteneğini kaybetmesidir; ilk kez bir hemipleji olgusunda Babinksi tarafından tanımlanmıştır. 22 Daha sonra anosognozinin sadece hemipleji değil, Parkinson, bunama, MS, Huntington hastalığı gibi nörodejenerasyonla giden MSS hastalıklarında da görülebileceği bildirilmiştir.…”
Section: Introductionunclassified